2018
DOI: 10.1101/362673
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of strategies for the assembly of diverse bacterial genomes using MinION long-read sequencing

Abstract: BackgroundShort-read sequencing technologies have made microbial genome sequencing cheap and accessible. However, closing genomes is often costly and assembling short reads from genomes that are repetitive and/or have extreme %GC content remains challenging. Long-read, single-molecule sequencing technologies such as the Oxford Nanopore MinION have the potential to overcome these difficulties, although the best approach for harnessing their potential remains poorly evaluated.ResultsWe sequenced nine bacterial g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 69 publications
0
55
0
Order By: Relevance
“…The mock communities were composed by the same ten microorganisms, but in different proportions (Table 1). With the aim of reducing the computational resources needed for the first screening of the selected assemblers, the GridION and Prome-thION datasets were subsampled to obtain an output comparable with recent genomic or metagenomic studies based on MinION (approximately 3 Gbp and 6 Gbp) 9,[34][35][36][37][38][39] . In general, mean read length remained the same in the subsampled datasets in comparison to the original sequencing data 15 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The mock communities were composed by the same ten microorganisms, but in different proportions (Table 1). With the aim of reducing the computational resources needed for the first screening of the selected assemblers, the GridION and Prome-thION datasets were subsampled to obtain an output comparable with recent genomic or metagenomic studies based on MinION (approximately 3 Gbp and 6 Gbp) 9,[34][35][36][37][38][39] . In general, mean read length remained the same in the subsampled datasets in comparison to the original sequencing data 15 .…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, however, ZymoBIOMICS genomes were used as a reference for carrying out the comparative analyses, due to their higher level of completeness. Although these reference genomes cannot be considered as "gold standards", Goldstein et al 9 demonstrated that the error profile obtained through hybrid assembly (ONT + Illumina MiSeq) was similar to the one obtained with MiSeq-only assembly, but the former resulted in higher contiguity. Reference genomes were gathered in a single multi-FASTA file to create a single-reference metagenome.…”
Section: De Novo Assemblymentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-genome sequencing (WGS) allows for timely detection and elucidation of AMR determinants in bacteria 7 . Third-generation sequencing has many advantages, like long read lengths, short time, and reduction of bias introduces through amplification by PCR-steps 8 . WGS has been used to investigate quinoloneresistant gonorrhoea outbreaks 9,10 in Kenya.…”
Section: Introductionmentioning
confidence: 99%